INVESTING IN THE DIGITAL ECONOMY: OPPORTUNITIES AND CHALLENGES IN A CONNECTED WORLD (Marketing Journal, 2026)
AbstractThe article analyzed investment directions in the digital economy and their impacton economic growth. Global investment volumes in fintech, e-commerce, artificialintelligence, cloud infrastructure, and cybersecurity were examined. Sectoraldevelopment trends and levels of investment activity were assessed. The expansion ofthe digital economy in Southeast Asia was reviewed. Key risk factors within theinvestment environment were identified and their priority levels were evaluated. Thefindings demonstrated the high return potential of digital markets. It was substantiatedthat sustainable development was ensured through risk management, diversification,and strategic investment planning.Keywords: digital economy, investment, fintech, AI, cybersecurity, e-commerce,cloud computing, digital infrastructure.